Experimental study of flow distribution in plate–fin heat exchanger and its influence on natural gas liquefaction performance. (5th June 2019) - Zhu, Jianlu; Zhang, Wei; Li, Yuxing; Ji, Peng; Wang, Wuchang
Highlights: Effects of gas–liquid ratio and tilt angle on gas–liquid distribution under tilt condition analyzed. Tilt condition aggravates mal-distribution of liquid phase. Sloshing can reduce the mal-distribution of fluid compared with tilting condition. Effects on heat transfer of mal-distribution of feed gas, nitrogen refrigerant, and mixed refrigerant simulated. Abstract: The mal-distribution of gas–liquid mixtures has serious influences on the heat-transfer performance of plate–fin heat exchangers (PFHEs), which would result in an adverse effect on the stable and efficient operation of a natural gas liquefaction plant. Therefore, it is necessary to investigate the phase distribution performance of PFHEs and its influence on the natural gas liquefaction performance. In this study, a two-phase flow distribution experimental system was built to investigate the flow distribution characteristics of a PFHE under different working conditions. The effects of gas–liquid ratio, tilt angle, and sloshing on the gas–liquid distribution were studied. In addition, the influences of mal-distribution of the feed gas, nitrogen refrigerant, and mixed refrigerant (MR) on the heat transfer and natural gas liquefaction performance were analyzed through the Aspen Muse software. The results showed that the greater the gas–liquid ratio and tilt angle, the more uneven the liquid flow distribution. The efficiency of the MR process in the tilt condition was reduced by 5.2% to 18.5% compared to that in the horizontal condition. Compared with the tilt working condition, the sloshing could reduce the unevenness of the flow distribution. To satisfy the natural gas liquefaction rate of more than 90%, the critical standard deviation values of flow distribution unevenness of the feed gas, nitrogen refrigerant, MR, and MR under the tilt condition were 8.33, 2.95, 4.42 (liquid phase), and 1.42 (liquid phase), respectively. In the process design, to ensure the output and liquefaction rate, the amount of the refrigerant circulation and power consumption should be kept at the margin of approximately 6% and 4% for the nitrogen expander and MR liquefaction processes, respectively.